Pengaruh Model Pembelajaran Kooperatif Tipe Two Stay Two Stray terhadap Hasil Belajar Kognitif Siswa pada Materi Sistem Pencernaan Manusia Kelas VIII MTS Al-Istiqamah Igobula Kecamatan Galela Selatan - Mandar, Nurjihan Hi; Tabaika, Rosita; Amin, Astuti Muh (IAIN Ternate, 2023)
The Two Stay Two Stray cooperative learning model is a learning model that can be used by teachers to create an active, effective and enjoyable learning atmosphere. The aim of this research is to determine the effect of the two stay two stray learning model on student learning outcomes in the human digestive system material for class VIII MTS AL-Istiqamah Igobula, South Galela District. This type of research is quasi-experimental research or Quasi Experiment. The population in this study was all class VIII, totaling 44 students consisting of two classes, namely class VIII-A and class VIII-B MTS AL-Istiqamah Igobula, South Galela District. The instruments used to measure student learning outcomes are pretest and posttest questions in the form of multiple choice, totaling 20 questions whose validity and reality have been tested. The results of research and data analysis show that the average value in the experimental class is 70.45, while the average value in the control class is 63.18 and the t test results show that there is a Sig. (2-tailed) obtained was 0.016 < α = 0.05, which means there is a significant difference between the experimental class and the control class. The conclusion of the research is that there is an influence of the two stay two stray cooperative learning model on students' cognitive learning outcomes in human digestive system material in class VIII Mts Al-Istiqamah Igobula. Keywords: Cognitive, Cooperative, Two Stay Two Stray, Learning Model, Biology.